Hurricanes Accelerate Dissolved Organic Carbon Cycling in Coastal Ecosystems - Yan, Ge; Labonté, Jessica M.; Quigg, Antonietta; Kaiser, Karl (Frontiers in Marine Science, 2020)
Extreme weather events such as tropical storms and hurricanes deliver large amounts of freshwater and associated dissolved organic carbon to estuaries and the coastal ocean, affecting water quality and carbon budgets. Hurricane Harvey produced an unprecedented 1000-year flood event in 2017 that inundated the heavily urbanized and industrialized Houston/Galveston region. Within a week, storm-associated floodwater delivered 71±24 Gg of terrigenous dissolved organic carbon (tDOC) to Galveston Bay and the Gulf of Mexico continental shelves. In-situ decay constants of 8.75-28.33 yr-1 resulted in the biomineralization of ~70% of tDOC within one month of discharge from the flood plain. The high removal efficiency of tDOC was linked to a microbial community capable of degrading a wide repertoire of dissolved organic matter (DOM). The efficient removal of tDOC demonstrated hurricane-induced flood events are unique and effective conduits to accelerate CO2 fluxes from estuarine watersheds and coastal seas.